2010
DOI: 10.1007/s11250-010-9690-3
|View full text |Cite
|
Sign up to set email alerts
|

Tick loads in cattle raised on sweet and sour rangelands in the low-input farming areas of South Africa

Abstract: The objective of this study was to compare tick loads and prevalence in Nguni and non-descript cattle in the sweet (palatable throughout the year) and sour (palatable only in the rainy season) communal rangelands of the Eastern Cape Province, South Africa. Engorged adult female ixodid ticks were collected and identified seasonally from 144 cattle raised on sweet and sour rangelands from August 2007 to April 2008. Three tick species were identified in the sweet and sour rangelands namely Rhipicephalus appendicu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
15
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 23 publications
5
15
0
2
Order By: Relevance
“…Contrastingly, Martinez et al (2006) found long curly hairs in animals favourable for higher tick loads as they allow ticks to hide from predators. On the other hand, short hairs discourage tick attachment to the animal's skin (Webb and David 2002;Marufu et al 2011a); hence, the current study showed a general trend of short-hair length during summer. This suggested that although hairs provide a means for ticks to attach to animals, seasonal variations determine high infestation.…”
Section: Resultsmentioning
confidence: 50%
See 1 more Smart Citation
“…Contrastingly, Martinez et al (2006) found long curly hairs in animals favourable for higher tick loads as they allow ticks to hide from predators. On the other hand, short hairs discourage tick attachment to the animal's skin (Webb and David 2002;Marufu et al 2011a); hence, the current study showed a general trend of short-hair length during summer. This suggested that although hairs provide a means for ticks to attach to animals, seasonal variations determine high infestation.…”
Section: Resultsmentioning
confidence: 50%
“…Heat stress affects production traits, reproductive abilities and may lead to infertility (Scholtz et al 2013). Marufu et al (2011a) highlighted the likely contribution of coat characteristics, such as colour, hair length and density, to tick infestation in cattle.…”
Section: Introductionmentioning
confidence: 99%
“…To cope with drought and forage seasonality, Nguni cattle have low nutrient requirements for maintenance, and excellent walking ability, which enables it to walk long distances in search of grazing and water [45,46]. Nguni also has good selective grazing and browsing abilities, which enables it to obtain optimal nutrition from the available natural vegetation, thus enabling it to survive under conditions that bulk grazers such as the European cattle breeds would find extremely testing [47;48]. Although it is small to medium sized, has meat quality characteristics that compare favourably with European beef breeds [47,49].…”
Section: Characterisation and The Adaptive Traits Of Indigenous Beef mentioning
confidence: 99%
“…[4] reported that Mashona cattle were more resistant to ticks and had high calving and weaning rate under marginal environmental conditions characterising most smallholder areas when compared to some exotic breeds. The resistance to ticks in sanga breed has been attributed to coat characteristics such as colour, hair length and density [48], grooming behaviour and delayed cutaneous hypersensitivity reaction to tick infestation [65]. An understanding of the mechanisms behind genetic resistance to ticks and TBD in livestock species could improve breeding programmes to develop animals that are more resistant and productive [62].…”
Section: Characterisation and The Adaptive Traits Of Indigenous Beef mentioning
confidence: 99%
“…Recently, there is evidence that Nguni cattle are less susceptible to ticks (Muchenje et al, 2008a;Marufu et al, 2011) and tick-borne diseases and nematodes (Xhomfulana et al, 2009). Nguni cattle are also better able to utilize rangeland feed resources (Collins-Lusweti, 2000;Mapiye et al, 2010a,b) and produce high quality meat that competes with meat from established beef breeds (Muchenje et al, 2008b).…”
Section: Introductionmentioning
confidence: 99%